Structural equation modeling test for relationship between selected leadership competencies and effective academic leadership styles - Shahmandi, Elham; Silong, Abu Daud; Ismail, Ismi Arif; Abu Samah, Bahaman; Omar, Zoharah (IDOSI Publications, 2013)
How can an academic leader become more effective? This research question is examined in the context of middle-level leadership in Malaysian research universities as World Class Universities. The purpose of this study is to examine the relationship between six leadership competencies and their relationship to four Effective Academic Leadership Styles (EALS) in the present context of globalization and academic excellence. Based on results in Structural Equation Modeling, contributions of leadership competencies depend on leadership styles in certain situations. Most of the competencies have relationships to EALS, except for two dimensions,organizational strategy and communication. Finally, systematic leadership development programs should be developed in research universities.